The Guild Composition for Modelling Fish Community in Banjaran River, Purwokerto - Windiariani Lestari; Dini Auliya Zayyana; Nuning Setyaningrum; Titis Amelia (Biosaintifika: Journal of Biology & Biology Education, 2018)
Over exploitation of consumed fishes causes declining of  targeted fish populations that will lead to a cascade effect to the guild compositions. The change of carnivorous, omnivorous and herbivorous fish populations drives to the food chain destructions and unstable ecosystems. The objective of this study was to build fish community modelling based on guild compositions. This study was conducted on fish communities in the Banjaran River. The data collected were species richness, the abundance of fish and the guild composition among carnivore, herbivore, and omnivore. Survey and purposive random sampling technique were applied and Banjaran River was divided into five sites based on the physical characteristics of the environment and fishing activities. Species richness data were analyzed by ANOVA, the composition of the carnivorous, omnivorous and herbivorous fish was analyzed descriptively based on the guild pyramides.  About 115 individuals consist of 17 species belong to 5 families were found. The species richness in the five sites in was relatively similar (P 0.05 (P = 0.269)). The fish community in site 3 had the balanced composition which was composed by 3% carnivores, 21.2% omnivores and 75.8% of herbivores.  This fish community modelling could be an an alternative way to manage fish community.  By controlling the carnivorous fish population, the natural resource especially fish as food resource will sustain and the species loss will be prevent.